Total glucosides of paeony prevents juxta-articular bone loss in experimental arthritis - Wei, Chen Chao (BioMed Central, 2013)
BACKGROUND: Total glucosides of paeony (TGP) is a biologically active compound extracted from Paeony root. TGP has been used in rheumatoid arthritis therapy for many years. However, the mechanism by which TGP prevents bone loss has been less explored. METHODS: TGP was orally administered for 3 months to New Zealand rabbits with antigen-induced arthritis (AIA). Digital x-ray knee images and bone mineral density (BMD) measurements of the subchondral knee bone were performed before sacrifice. Chondrocytes were observed using transmission electron microscopy (TEM). Histological analysis and mRNA expression of receptor activator of nuclear factor-B ligand (RANKL) and osteoprotegerin (OPG) were evaluated in joint tissues. RESULTS: The BMD value in TGP rabbits was significantly higher compared with that seen in the AIA model rabbits. In addition, the subchondral bone plate was almost completely preserved by TGP treatment, while there was a decrease in bone plate integrity in AIA rabbits. There was less damage to the chondrocytes of the TGP treated group. Immunohistochemical examination of the TGP group showed that a higher percentage of TGP treated chondrocytes expressed OPG as compared to the chondrocytes isolated from AIA treated animals. In contrast, RANKL expression was significantly decreased in the TGP treated group compared to the AIA group. In support of the immunohistochemistry data, the expression of RANKL mRNA was decreased and OPG mRNA expression was enhanced in the TGP group when compared to that of the AIA model group. CONCLUSION: These results reveal that TGP suppresses juxta-articular osteoporosis and prevents subchondral bone loss. The decreased RANKL and increased OPG expression seen in TGP treated animals could explain how administration of TGP maintains higher BMD.